Method of preparing unfixed ciliates for scanning electron microscopy without noticeable artifacts - Ishida, Hideki; Yamamoto, Kousei; Yano, Yuki; Ikeda, Kenichi; Gaponova, Liudmyla; Higuchi, Rina; Kolosiuk, Andrii; Suzaki, Toshinobu (Frontiers in Protistology, 2023)
Water freeze-drying of biological samples has long been considered unfeasible as a sample preparation method for scanning electron microscopy (SEM) owing to the formation of damaging ice crystals. Contrary to this assumption, however, when live ciliates in water were frozen in contact with pre-cooled copper blocks in this study, they could be freeze-dried without artifact formation, although the success rate was only about 10%. This method offers several advantages over the traditional approach of chemical fixation followed by dehydration and drying. First, the degree of sample shrinkage associated with sample preparation was much lower than with chemical fixation. Second, contractile ciliates such as Spirostomum and Lacrymaria could be sampled in their elongated state, and the metachronal waves of cilia on the cell surface were well preserved.Moreover, this method requires no special equipment and only a few hours at most for sample preparation before SEM observation. Thus, although this method needs to be improved to increase the success rate in the future, it can be used to prepare samples for SEM observation that could not be prepared by other methods.